Reproductive Health Experiences of Syrian Refugees Residing in Jordan - Malena Price; Reema Safadi; Dennis Clements (Journal of Midwifery & Reproductive Health, 2020)
Background & aim: In 2016, 28% of Syrian women residing in Amman experienced at least one unplanned pregnancy, and 17% did not access antenatal care for pregnancy.  This study aimed to elucidate the imminent need for greater accessibility to comprehensive sexual and reproductive healthcare among Syrian refuges residing in Jordan. Methods: This ethnographic case study was conducted in 2017 in order to understand the reproductive health experiences of 21 male and female Syrian refugees residing in Amman. Participants were selected based on purposive sampling. Study interviews examined the experiences of participants regarding their pregnancy outcomes, influencing factors for their reproductive decisions, and gaps in sexual and reproductive healthcare in Amman. Results: Participants indicated great SRH need specifically related to the education on contraceptive methods. Participants confirmed that reproductive health services in Syria were more accessible, affordable, and comprehensive compared to health services in Jordan. The greatest contributors to gaps in care for participants were financial constraints and apathy regarding refugee welfare among providers in Jordanian public facilities. All study participants placed great value on family and reproduction. The most commonly used methods of contraception among participants were the oral contraceptive pill (OCP) and coitus interruptus. Over 75% of participants began trying to conceive right after marriage. Conclusion: Increases in access to comprehensive sexual and reproductive healthcare among refugees in low-resource, humanitarian settings is a healthcare priority. The findings can influence the policies affecting family planning and reproductive health mechanisms provided for migrants in Jordan in both public and private hospitals.